Almond and walnut shell-derived biochars affect sorption-desorption, fractionation, and release of phosphorus in two different soils. (February 2020) - Hemati Matin, Narges; Jalali, Mohsen; Antoniadis, Vasileios; Shaheen, Sabry M.; Wang, Jianxu; Zhang, Tao; Wang, Hailong; Rinklebe, Jörg
Abstract: Effective soil phosphorus (P) management requires higher level of knowledge concerning its sorption-desorption, fractionation, and release, as well as its interactions with soil amendments including biochar (BC). The purpose of this research was to investigate the influence of two different BCs, derived from almond and walnut shell, on P sorption-desorption and its redistribution among the geochemical fractions in two different soils. The BCs were applied to the soils in four doses (0, 2.5, 5, and 10% w/w) and the mixtures were incubated for one month. Phosphorus sorption increased due to the addition of BCs. Phosphorus sorption data fitted well the Freundlich isotherm and were simulated by the PHREEQC software. Biochar addition increased total P and the added P was mainly distributed in the exchangeable, Fe/Al–P and the residual fractions. Also, BC addition resulted in an increase in the water-soluble-, mobile-, and Olsen-P, making P more available for plant uptake. The kinetics data were well described by the simple Elovich, pseudo-second-order, and intra-particle diffusion equations. Walnut BC-added soils had higher P sorption capacity than those added with the almond BC. The results suggest that BC binds soil P and releases it gradually back into solution, making it thus available to plants; this renders the studied BCs promising materials for protecting P from being lost out of soil. Future research must be conducted over longer-term experiments that would study P dynamics in BC-added soils under real field conditions. Graphical abstract: Image 1 Highlights: Almond and walnut shell biochars (BCs) increased P sorption in alkaline soils. Biochar released previously bound P gradually back into solution. Walnut BC-added soils sorbed more P than soils added with almond BC. Biochar-added P was distributed in the residual and exchangeable fractions. BC addition to soil resulted in increased water-soluble-, mobile-, and Olsen-P.